Treatment of gingival recession by coronally advanced flap in conjunction with platelet-rich fibrin or resin-modified glass-ionomer restoration: A clinical study - Sudheer Ramireddy; Jaideep Mahendra; Vijayalakshmi Rajaram; Geetha Ari; Anil Kumar Kanakamedala; Dhanadivya Krishnakumar (Wolters Kluwer Medknow Publications, 2018)
Aims: The aim of this study is to compare the outcome of coronally advanced flap (CAF) along with the use of platelet-rich fibrin (PRF) versus CAF in conjunction with a resin-modified glass-ionomer cement (RmGIC) for the management of Millers Class I and Class II gingival recession coupled with noncarious cervical lesions (NCCLs). Materials and Methods: Single and multiple Miller's Class I and Class II gingival recessions were chosen for the study. Twenty participants with total of 78 sites associated with NCCL bilaterally in the anterior and premolar region of maxilla were selected. Thirty-nine sites were treated with CAF and PRF and the remaining 39 sites were treated with CAF and RmGIC. Clinical parameters such as probing pocket depth, relative gingival recession, relative clinical attachment level, NCCL height, NCCL width, width of keratinized tissue, and keratinized tissue thickness were measured at baseline, 90th, and 180th day in both the groups. The presence or absence of dentin sensitivity (DS) was determined at baseline and 180th day. Results: Both the groups showed optimal root coverage, with statistical significant difference in thickness of keratinized gingiva in Group I when compared to Group II from baseline to 90th day and from baseline to 180th day and also from 90th to 180th day. On comparing the DS between Group I and Group II from baseline to 180th day, Group II showed greater reduction in dentinal hypersensitivity as compared to Group I. Conclusion: The use of PRF along with CAF showed increased thickness of the keratinized tissue and the utilization of RmGIC resulted in decreased DS. Hence, the combination of CAF and PRF or CAF and RmGIC could provide a better treatment option in the management of gingival recession that is of esthetic concern.